Economic Collaborative Activities to the Detriment of the State’s Sustainable Development: Characteristics of the Criminal Offense and Peculiarities of Judicial Practice - Luhovyi, Viktor; Niedov, Roman; But, Yurii; Trofimtsov, Vladyslav; Shkoda, Vlada (European Journal of Sustainable Development, 2025)
The aim of this research is to analyze the elements of the crime enshrined in the Art. 111-1 of the Criminal Code of Ukraine (CCU) from the perspective of encroachment on the sustainable development of Ukraine, the specifics of qualifying economic collaborationism, as well as court practice on this issue. The indicated methods were applied in the course of the research: formal and logical; dialectical; monographic; dogmatic; systemic-structural; statistical; legal modeling; summarization. Throughout legal characteristics of collaborationism is provided. The focus is directed to the features of the objective side of the crime that reflects the most common options for voluntary cooperation with the aggressor state during temporary occupation. The need to provide legal certainty to the concept of “voluntary” cooperation with the aggressor State is substantiated. It is noted that the subjective side of collaborationism is marked by direct criminal intention, and some parts of this provision also have a special purpose. Types and forms of collaborative activities are highlighted. The features of economic collaborationism are considered. The judicial practice on this issue is studied. It is concluded that the longer our state’s territories remain under occupation, the more collaborationism spreads, hindering one of the main objectives of stable country’s developing: conflict and post-conflict resolution of public security. Keywords: collaborationism, economic collaborationism, sustainable development, Criminal Code of Ukraine, judicial practice.